МОНГОЛ ДАХЬ ЕВРОП СУДЛАЛЫН ӨНӨӨГИЙН БАЙДАЛ БА ТУЛГАМДАЖ БУЙ АСУУДЛЫН СУДАЛГАА - Г.Золзаяа,; Б.Одгэрэл,; Б.Галиндэв,; С.Одхүү,; Н.Хосбаяр, (Politology, 2023)
This study aims to determine the level of knowledge on the European Union, a region of major players in international relations, world politics and diplomacy, its multifaceted activities in the world, the current situation, the challenges it faces and the real trends in development of undergraduate students study Political Science, International Relations and Law, to compare the views and positions of European scholars, researchers and researchers, and to analyze and comment on the content of the European Studies curriculum in the International Relations programs implemented in Mongolia.